2021
DOI: 10.1007/s12144-021-02333-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between COVID-related parenting stress, nonresponsive feeding behaviors, and parent mental health

Abstract: has disrupted the lives of families across the United States and all over the world. Stress is known to have a negative impact on parent-child feeding interactions; hence, the purpose of this study is to examine how COVID-related parenting stress, which was measured using a newly developed scale, is related to parent mental health, nonresponsive feeding, and children's self-regulation of eating. 119 parents of children ages 2-7 years old filled out questions about COVID-related parenting stress, mental health,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 48 publications
4
22
0
1
Order By: Relevance
“…This is consistent with previous studies [17,41]. Stress can effectively interfere with parents' ability to observe children's behavior and limit children's ability to regulate their energy intake [29]. Coercive control practices, for example, can reduce vegetable intake over time [42].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with previous studies [17,41]. Stress can effectively interfere with parents' ability to observe children's behavior and limit children's ability to regulate their energy intake [29]. Coercive control practices, for example, can reduce vegetable intake over time [42].…”
Section: Discussionsupporting
confidence: 88%
“…The articles by Caroline et al [25] and Jansende et al [21]. were classified as high quality by the NOS standard, whereas the remaining six articles [26][27][28][29][30][31] were classified as medium quality (in Additional File 1). Table 1 shows the study's characteristics and significant findings.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the relationship between mothers' socio-demographic characteristics and total stressors facing them and total coping scores, the current study showed statistically significant differences were found between mothers' work, family income, total stressors facing them, and total coping scores. (Frankel et al, 2021) who conducted a study about the relationship between COVID-related parenting stress, nonresponsive feeding behaviors, and parent mental health was congruent with the present finding. From the researchers' point of view, parents will experience a higher stress level if they were working during the pandemic, which may best be explained by the need to juggle multiple roles, such as being a caregiver, educator, and employee, simultaneous.…”
Section: Regardingsupporting
confidence: 85%
“…Evidence shows that parenting stress and exhaustion also increased, especially for mothers of young children ( 5 ). Consistent with pre-pandemic data, parenting stress and exhaustion were significant predictors of adverse mental health ( 6 8 ).…”
Section: Introductionsupporting
confidence: 72%